Risk Control Strategy in Public Financial Management in NorthSumatra - Irawan; Ilham Ramdhan Nasution; Ahmad Sani (Proceedings of The International Conference on Computer Science, Engineering, Social Science, and Multi-Disciplinary Studies, 2025)
Public financial management is a vital element in realizing transparent, accountable, andservice-oriented governance. However, the complexity of the planning, budgeting, implementation, andaccountability processes at the regional level often gives rise to various risks that can hamper the effectiveness ofgovernment administration. This study aims to analyze risk control strategies in public financial management inNorth Sumatra Province, identify the most dominant types of risks, and evaluate the effectiveness of controlmechanisms implemented by the regional government. The research method uses a qualitative approach withdata collection techniques through documentation studies, interviews with regional financial managementofficials, and analysis of financial reports and supervisory findings. Data analysis was conducted descriptivelywith reference to the enterprise risk management (ERM) framework and the Government Internal ControlSystem (SPIP). The results show that the main risks in public financial management in North Sumatra includethe risk of inaccurate planning, budget implementation discrepancies, administration and procurement risks, andthe risk of low compliance with standard procedures. Although the regional government has implemented anumber of control measures, such as increasing the role of APIP, strengthening SPIP, and utilizing informationtechnology, their effectiveness remains limited due to variations in human resource capacity, suboptimal crossunit coordination, and a weak risk management culture. This study concludes that risk control strategies in NorthSumatra need to be directed at strengthening data-based risk identification, integrating oversight with planningand budgeting processes, improving staff competency, and implementing an integrated information system thatsupports sustainable control. The findings of this study are expected to serve as a reference in developing morecomprehensive risk management policies in the public sector, particularly in improving the accountability andeffectiveness of regional budget management